Wales - Colson, Mary. (Chicago : Heinemann Library, 2012)
An introduction to Wales, providing information on the country's geography, history, culture, landmarks, wildlife, people, politics, and more, with maps, graphs, foreign language phrases, and a time line.
Introducing Wales -- History : becoming Wales -- Regions and resources : water world and working life -- Wildlife : protecting nature -- Infrastructure : politics and people -- Culture : national identities -- Wales today.
Includes bibliographical references (p. 44) and index.
6.9
3-6.
3-6
Keywords: Wales -- Juvenile literature; Wales; Wales